On tenses as speech-act-level functions - Patrick Caudal (Isogloss)
This paper aims at demonstrating the validity of a two-pronged hypothesis: (i) that the aspectual viewpoint content of the so-called ‘narrative imparfait’ (NIMPF) does not bear on the verb it marks (i.e., it does not combine with the event predicate denoted by said verb) but that, therefore, (ii) it must operate at a higher, discursive semantic level. To substantiate the above hypothesis, the paper first focuses on diachronic and synchronic evidence suggesting that the NIMPF does not contribute aspectual meaning at the sentence semantics-level – showing notably that it behaves like a ‘viewpoint neutral’ tense with respect to the verb it marks. The paper then discusses synchronic, discursive evidence supporting the view that the NIMPF actually indicates a partial, discourse-structurally incomplete, ‘ongoing’ narrative act. From these two facts, the paper concludes that NIMPF utterances refer to imperfectively viewed narrative speech act events, and constitute a separate speech act-level conventionalized reading of the imparfait, applying an imperfective viewpoint meaning to relational speech act functions, i.e., to rhetorical relations. It is argued that they should be endowed with a speech act event argument, and constitute an abstract type of event predicate which the viewpoint meaning of the NIMPF takes as its input.